2017
DOI: 10.1097/meg.0000000000000972
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of correlations between lipid profile and different computed tomography fatty liver criteria in the setting of incidentally noted fatty liver on computed tomography examinations

Abstract: Incidental reporting of fatty liver on NECT/CECT should prompt consideration of clinical follow-up and lipid profile testing in an otherwise asymptomatic patient. Additional metrics for the diagnosis of steatosis in CECT exam should also be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…Previous studies have reported that hepatic steatosis on CT is associated with dyslipidemia, the presence of diabetes, alcoholism, and hypertension [ 15 , 16 ]. Other recent studies have shown that incidentally detected hepatic steatosis determined by various CT criteria is associated with an abnormal lipid profile, abnormal liver function, and certain comorbidities [ 8 , 9 ]. In our study, we sought to validate the association in a health screening population, specifically in the setting of NAFLD, by excluding those with hepatitis B or C virus infection or alcoholism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have reported that hepatic steatosis on CT is associated with dyslipidemia, the presence of diabetes, alcoholism, and hypertension [ 15 , 16 ]. Other recent studies have shown that incidentally detected hepatic steatosis determined by various CT criteria is associated with an abnormal lipid profile, abnormal liver function, and certain comorbidities [ 8 , 9 ]. In our study, we sought to validate the association in a health screening population, specifically in the setting of NAFLD, by excluding those with hepatitis B or C virus infection or alcoholism.…”
Section: Discussionmentioning
confidence: 99%
“…Splenic attenuation was measured by averaging HU values of three 2 cm 2 circular ROIs placed at three different sites in the middle third of the spleen. To measure hepatic and splenic attenuation, ROIs were placed to exclude macroscopic hepatic vessels, biliary structures, and any focal liver lesions, and they were at least 5–10 mm away from the periphery of the liver [ 8 ] ( Figure 2 ). The same measurement process was performed in two sessions, and each session was scheduled a week apart to minimize recall bias.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite increasing awareness in recent years, the prevalence is increasing and its prevalence varies relying upon the country, age, sex, ethnicity, and related risk factors. NAFLD is believed as one of the most well-known reasons for chronic liver disease all over the world [2,3].…”
Section: Introductionmentioning
confidence: 99%